Aerobic Vaginitis Caused By Streptococcus &Bgr;- Hemolyticus and Staphylococcus Epidermidis in a 26-Year-Old Woman with a History of Frequent Antibiotics Administration - Achdiat PA; Saraswati AL; Handayani Y; Rowawi R; Maharani RH (International Journal of Women's Health)
Pati Aji Achdiat, Amalia Laksmi Saraswati, Yulisa Handayani, Rasmia Rowawi, Retno Hesty Maharani Department of Dermatology and Venereology, Faculty of Medicine Universitas Padjadjaran – Dr. Hasan Sadikin Hospital, Bandung, West Java, IndonesiaCorrespondence: Pati Aji Achdiat, Department of Dermatology and Venereology, Faculty of Medicine, Universitas Padjadjaran – Dr. Hasan Sadikin Hospital, Jl. Pasteur 38, Bandung, West Java, Indonesia, 40161, Email pati.aji.achdiat@unpad.ac.idAbstract: Aerobic vaginitis (AV) is a form of vaginitis caused by the presence of aerobic bacteria, primarily group B Streptococcus, Escherichia coli, Enterococcus faecalis, Streptococcus viridans, and Staphylococcus epidermidis. This condition is characterized by clinical signs of acute inflammation, including vaginal redness, burning, increased vaginal secretions with a pH of 5, sticky vaginal discharge, leukocyte infiltration, and vulvar pruritus, which is defined as itching and irritation, and commonly occurs in individuals between the age of 15– 30 years and 31– 45 years. The report presents a case of AV caused by Streptococcus β-hemolyticus and Staphylococcus epidermidis in a 26-year-old female patient at Hasan Sadikin Hospital, Bandung. The treatment process includes the administration of amoxicillin 500 mg three times daily for 14 days. The patient was unmarried, routinely performed vaginal douching with betel soap, and frequently used a panty liner. Subsequently, a history of frequent antibiotic use was reported, however, the specific names of previously administered antibiotics remain unknown, except for clindamycin, which is the only agent specifically recalled. The patient also had a history of high exposure to stressors and underwent a bacterial culture examination taken from the vaginal introitus, which showed the presence of Streptococcus β-hemolyticus and Staphylococcus epidermidis. This case highlights the significance of AV in the differential diagnosis of vaginal infections, especially in atypical patient populations, and emphasizes the need for appropriate diagnostic measures such as bacterial culture to guide effective treatment strategies.Keywords: aerobic vaginitis, streptococcus β-hemolyticus, staphylococcus epidermidis, aerobic vaginitis